Argentina's Distributional Failure: The role of Integration and Public Policies - Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2003)
This paper documents the income distribution changes experienced by Argentina during the last decades. Inequality substantially increased, and despite economic growth during some periods, poverty also went significantly up. Two types of episodes have shaped Argentina's income distribution: deep macroeconomic crisis and periods of openness and integration. The sizeable raise in inequality in the 90s seems to be associated to reallocations against unskilled-labor intensive sectors, and especially to skilled-biased technological change within most sectors, both factors stimulated by the process of economic integration. The depth and speed of the reforms and the absence of public policies to ease the transition contributed to the particular severity of the income distribution changes in Argentina.
Keywords: C15; D31; I21; J23; J31; 330; inequality; distribution; globalization; integration; wages; education; Argentina